Distillers dried grains with solubles from corn in diet of japanese quails - Bittencourt, Tatiana Marques; D’Ávila Lima, Heder José; Valentim, Jean Kaique; Martins, Ana Carolina da Silva; Moraleco, Débora Duarte; Vaccaro, Brenda Chagas (Acta Scientiarum. Animal Sciences, 2019)
The objective of this study was to evaluate different inclusion levels of distillers dried grains with solubles (DDGS) from corn in the diet of quails. A total of 210 japanese quails (Coturnix coturnix japonica) were distributed in a completely randomized design of five treatments and six replicates, with seven quails per experimental unit. The treatments used were: control feed; inclusion of 5, 10, 15 and 20% of DDGS. The variables assessed were: feed intake, feed conversion per dozen and egg mass, egg production, egg weight, specific gravity, yolk color and economic analysis. Data were analyzed by regression model and Dunnett’s test at 5% probability. For individual feed intake, laying rate, and feed conversion per egg mass, specific gravity and yolk color by color fan, there was effect caused by inclusion of DDGS (p < 0.05), but the other variables did not show significant difference. By Dunnett’s test, for feed intake, feed conversion per egg mass, specific gravity and digital colorimeter’s L parameter, there was effect (p < 0.05). As for economic analysis, DDGS presented low cost. It can be concluded that DDGS can be used in feed at a 20% level without impairing the performance and quality of quails eggs.